PERKEMBANGAN, PENGAWASAN DAN PENGENDALIAN BANK SYARIAH DI INDONESIA - Fitriani Fitriani; Nur Nasrina; Heri Sunandar (J-EBI Jurnal Ekonomi dan Bisnis Islam, 2023)
Islamic banking is a banking system developed based on Islamic law. Indonesia, where the majority of the population is Muslim, provides ample space for the development of Islamic banks. The development of Islamic banking in Indonesia has become a benchmark for the successful existence of the Islamic economy. The Sharia Banking Supervisory Authority in Indonesia examines Islamic banking supervision from a normative juridical perspective. Regulation and supervision of Islamic banking based on Law Number 3 of 2004 concerning Amendments to Law Number 23 of 1999 concerning Bank Indonesia and Law No. 21 of 2008 are the authority of BI. After the enactment of Law No. 21 of 2011 concerning the OJK, sharia banking supervision, which was originally the authority of BI, shifted to the OJK. The internal control system implemented must be in accordance with applicable policies and regulations so that the results obtained can have a positive impact on the financing transactions carried out.